Computational Software: Polymer Chain Generation for Coarse-Grained Models Using Radical-Like Polymerization (Communications in Computational Physics, 2018)
This paper presents major improvements in the efficiency of the so-calledRadical-Like Polymerization (RLP) algorithm proposed in "Polymer chain generationfor coarse-grained models using radical-like polymerization" [J. Chem. Phys. 128(2008)]. Three enhancements are detailed in this paper: (1) the capture radius of aradical is enlarged to increase the probability of finding a neighboring monomer; (2)between each growth step, equilibration is now performed with increasing the relaxationtime depending on the actual chain size; (3) the RLP algorithm is now fully parallelizedand proposed as a "fix" within the "Lammps" molecular dynamics simulationsuite.
Keywords: Molecular dynamics (MD); coarse grained polymer model; LAMMPS; polymer; parallel computing.